Cześć proszę o pomoc !
Rozwiąż równanie :

a)y+3/2- (1-y) =3,5

b) 1/5(y-3) - 2/3( y- 3/5)+ 1/3=2/5-1/3(2y-3)

c)(2y+4 )/4 =1/2y+1

d)(y-2)/3 + 1/15 - (2y-5)/3 = (8-4y)/5

e) (y-5)/2 + (2y+3)/5 +1/3 = (y+7)/15 + y/2

f) 0,83x+0,82= 0,23x+ 1,52

g) 0,6x + 2(0,1x-o,1) = 0,2 (x+1)

h) 0,7(x+2) = o,4(x+1)+ 0,3x+1

i) 0,15(2x+4) = 2(1,3+0,3x) - 0,6

j) o,1 (x+1) - 0,05(3x-10)= 0,4 - 0,35x

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T20:26:26+01:00
A)y=3/2
b)y=6 i 1/3
d)y=1 i 5/7
e)y=6,1
f)x=1,17
g)x=0,07
h)0=0
i)x=-8,67
j)x=2,67